Rancang Bangun Sistem Monitoring Level Permukaan Air Pada Simulator Level Air - Totok Soehartanto; Herry Sufyan Hadi; Muhammad Hisbun Nasrirrokhim (Jurnal Otomasi Kontrol dan Instrumentasi, 2026)
Water level monitoring is generally still done manually. To improve monitoring effectiveness, a real-time water level monitoring system was designed using an aquarium simulator. This simulator represents three scenario conditions: Normal, Alert, and Danger. This system uses an ultrasonic sensor to measure water levels, a microcontroller as a data processor, and a wireless communication module to transmit data to a central server. The collected data is displayed on a local display for easy access by readers. Through testing, this system demonstrated an accuracy of 96,43% with a swift data transmission time of 0,05-0,07 seconds. The implementation of this system provides an effective automated monitoring solution, minimizing the need for manual observation, and this system has the potential to improve flood risk mitigation through more accurate and responsive early warnings.